2016
DOI: 10.3892/mmr.2016.6051
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of resveratrol on the adhesion, migration and invasion of human bladder cancer cells

Abstract: Abstract.Resveratrol is a polyphenolic compound, which has been revealed to induce apoptosis in numerous human cancer cells; however, the effects of resveratrol on the migration and invasion of human bladder cancer cells have not been reported. The present study aimed to evaluate the anti-metastatic potential of resveratrol against bladder cancer and its mechanism of action. The results indicated that resveratrol inhibits the adhesion, migration and invasion of bladder cancer cells in a dose-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Resveratrol is a polyphenolic compound found in grapes, berries, and peanuts . Regarding bladder cancer, it has already been demonstrated that resveratrol decreases cell viability, induces apoptosis, inhibits cell migration and induces cell cycle arrest in vitro (Stocco et al 2002;Lin et al 2012;Bai et al 2017). Furthermore, the antitumor potential of this natural product has been described in many tumor types (Ji et al 2015;Mohapatra et al 2015;Nie et al 2015;Selvaraj et al 2016).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Resveratrol is a polyphenolic compound found in grapes, berries, and peanuts . Regarding bladder cancer, it has already been demonstrated that resveratrol decreases cell viability, induces apoptosis, inhibits cell migration and induces cell cycle arrest in vitro (Stocco et al 2002;Lin et al 2012;Bai et al 2017). Furthermore, the antitumor potential of this natural product has been described in many tumor types (Ji et al 2015;Mohapatra et al 2015;Nie et al 2015;Selvaraj et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the antitumor potential of this natural product has been described in many tumor types (Ji et al 2015;Mohapatra et al 2015;Nie et al 2015;Selvaraj et al 2016). Regarding bladder cancer, it has already been demonstrated that resveratrol decreases cell viability, induces apoptosis, inhibits cell migration and induces cell cycle arrest in vitro (Stocco et al 2002;Lin et al 2012;Bai et al 2017). Resveratrol is also able to reduce tumor growth in vivo (Bai et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol, found in many foods such as grape, is a phytoalexin with antioxidant, anti-inflammatory, and anti-cancer properties (Bai et al, 2017). The beneficial effects of resveratrol on male reproductive system have been approved by many authors addressing the antioxidant properties of this natural product.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be extracted from the traditional Chinese plant Polygonum cuspidatum (5). Resveratrol has exhibited promising anticancer activity against breast cancer, ovarian cancer, leukemia, prostate cancer, liver cancer, melanoma, head and neck squamous cell carcinoma, thyroid cancer, and bladder cancer, via regulating cancer-related gene expression or cancer-associated signaling pathways (5)(6)(7)(8)(9)(10). The anticarcinogenic action of resveratrol is associated to its ability to neutralize reactive oxygen species (ROS) and to modulate cellular processes, such as apoptosis and cancer cell proliferation and differentiation (11).…”
Section: Introductionmentioning
confidence: 99%